QUEEN OF THE AGRESTE: FROM COTTON PRODUCTION TO THE PROVISION OF SERVICES - da Silva, Isadora Duarte; Salvador, Diego Salomão Candido de Oliveira (Seven Editora, 2025)
The objective of this work was to analyze the progression of the services offered in the city of Nova Cruz, from the 1950s to the present day. The methodology used was the theoretical and historical review regarding the evolution of the services provided in the municipality of Nova Cruz-RN, as well as field visits, in order to map the main services of the city, photograph and observe the urban dynamics generated by them. In addition, the REGIC methodologies were revisited and analyzed to understand the centrality of Nova Cruz. The results showed that cotton was the economic activity that gave visibility to the city, however, with its decline, the space was used by other services: supermarket chains, retail and wholesale segment, universities, federal institutes, national institute of social security, regional directorate of education and culture, banks and others. It is concluded that the absence of these services and their concentration in Nova Cruz, reinforce their importance in the region. DOI: https://doi.org/10.56238/sevened2024.037-208